Victimhood of the Nation as a Legally Protected Value in Transitional States – Poland as a Case Study - Gliszczyńska-Grabias, Aleksandra; Śledzińska-Simon, Anna (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
The memory of the past is always vital for building national identity in transitional contexts. Yet, the preservation of a particular representation of the national history may lead not only to distortion of the self-identification process, but also to distortion of rights protection. Taking Poland as a case study, we aim to explain mechanisms of using criminal laws for historical assessment and show instances when victimhood became a legally protected value used to justify limitations of free speech and academic research. We argue that the law criminalising defamation of the Polish Nation, and also the decision of the Polish Constitutional Tribunal, were symptoms of frustration and fear against opening and engaging in an honest public debate on recent history, which is necessary for establishing not only the fundamentals of transitional justice, but more importantly, for building mutual trust in a democratic society.
Keywords: ofiara; pamięć; Trybunał Konstytucyjny; Polska